Komunikasi Dialog Dalam Praktik Kehumasan Menggunakan Sosial Media di Kota Bandar lampung - Razak, Razie; Mupiza , Bintar; Yasirandi, Rahmat (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This community engagement programme has been launched in response to the challenges of public communication in the digital age, such as the spread of fake news, rising negative sentiment, and the public’s limited ability to engage in constructive dialogue on social media. As a partner, the Kolaborator Kebaikan Foundation seeks to strengthen the community’s skills in dialogic communication in order to foster ethical and participatory public interaction. Through a cultural approach and the use of communication technology, this programme enhances dialogue-based communication literacy. Telkom University, in collaboration with the Kolaborator Kebaikan Indonesia Foundation, organises training that applies the principles of mutuality, closeness, empathy, risk, and commitment, encompassing the stages of preparation, awareness-raising, training, mentoring, evaluation, and dissemination. Data was collected through pre-tests, post-tests, observations and focused group discussions. The material covered dialogic communication, digital ethics and the management of interactions on social media. The evaluation results showed an improvement in participants’ competencies, reflected in an increase in the average comprehension score from 64 to 86.5, and 20 participants reported a better understanding of the principles of dialogic communication and social media ethics following the training. These findings indicate an improvement in participants’ ability to manage differences of opinion and foster more constructive interactions in the digital space; consequently, this programme helps to strengthen the institution’s relationship with the public by enhancing the community’s capacity for dialogic communication.